Solve each of the following equations by using the method of completing the square:3x2 - 2x - 1 = 0

Given: 3x2 - 2x - 1 = 0

9x2 - 6x = 3 (multiplying both sides by 3)

using a2 - 2ab + b2 = (a - b)2

(taking square root on both sides)

3x - 1 = 2 or 3x - 1 = - 2

3x = 3 or 3x = - 1

Hence the roots of equation are

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Knowing the Nature of Roots44 mins
Take a Dip Into Quadratic graphs32 mins
Foundation | Practice Important Questions for Foundation54 mins
Nature of Roots of Quadratic EquationsFREE Class
Getting Familiar with Nature of Roots of Quadratic Equations51 mins
Quadratic Equation: Previous Year NTSE Questions32 mins
Champ Quiz | Quadratic Equation33 mins
Balance the Chemical Equations49 mins
Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses